Investigating the Influence of Social Media Platforms on the Evolution of English Slang - Norqulova, Dilnoza Shavkat qizi; Dalieva, Madina Khabibullaevna (The Lingua Spectrum, 2026)
This article examines how social media platform affordances shape the diffusion, stabilization, and meaning change of English slang. Slang is treated as socially indexed vocabulary and formulaic patterns that circulate through communities, gain visibility, undergo semantic drift, and either become mainstream or decline. The paper argues that contemporary slang evolution is increasingly platform-driven: character limits, hashtags, algorithmic feeds, video remix tools, and community moderation influence which forms spread, how fast they travel, and what meanings become conventional. A mixed-method research design is proposed: cross-platform corpus sampling (X/Twitter, TikTok, Instagram, Reddit, YouTube), quantitative tracking of lexical items over time (frequency, dispersion, burstiness), and qualitative discourse analysis of pragmatic functions (stance, humor, in-group marking, mitigation). The article synthesizes key mechanisms – memetic templating, influencer amplification, audio-based replication, cross-platform migration, and context collapse – and offers operational criteria for identifying meaning change and enregisterment. Implications are discussed for language teaching, digital literacy, and responsible translation.